BAGAIMANA RESONANSI EMOSIONAL MENDORONG KETERLIBATAN KONSUMEN DALAM PEMASARAN DIGITAL: TINJAUAN LITERATUR SISTEMATIS - Maulida, Sulistiani; Widjajanta, Bambang; Hendrayati, Heni; Juniati, Chealsy (Journal of Information System, Applied, Management, Accounting and Research, 2026)
This systematic literature review examines how emotional resonance drives consumer engagement in digital marketing contexts. Following PRISMA 2020 guidelines, a comprehensive search of Scopus database yielded 1,247 records (2020-2025), with 15 peer-reviewed studies included after systematic screening and quality assessment. Thematic synthesis reveals three dominant conceptualizations: emotional resonance as a dual-process construct (cognitive and affective), as specific emotional outcomes (brand love, attachment), and as experiential affective states. Empirical evidence demonstrates robust positive relationships with behavioral engagement showing the strongest effects (mean β = 0.48), followed by emotional (β = 0.42) and cognitive engagement (β = 0.29). Key antecedents include content authenticity, storytelling quality, personalization, platform affordances, and consumer characteristics. The S-O-R framework (27%), brand relationship theories (33%), and experiential marketing (20%) dominate theoretical perspectives. Critical gaps exist in longitudinal research, negative emotions, emerging technologies (AI, VR, metaverse), and cross-cultural contexts. Practically, brands should prioritize authentic storytelling, balance personalization with privacy, and leverage interactive platforms. This review provides the first comprehensive synthesis consolidating fragmented knowledge on how emotional resonance mechanisms drive consumer engagement in digital marketing.